Make. - Dougherty, Dale (Make.CO, 2022)
It's been another tumultuous year in the world of embedded electronics: Supply chain snags have scarcely relented, while new chips jostle for position as the go-to for makers. In this issue of Make:, we look at how scarcity is affecting the industry and impacting new and stalwart boards alike. We explore how RISC-V chip architecture is putting open silicon in the hands of makers. And if your favorite board is out of stock, we offer smart substitutes. Also included is our annual Make: Guide to Boards comparing 79 of the hottest microcontrollers, single-board computers, and FPGAs â?? with an emphasis on those you can actually get your hands on.